1987
DOI: 10.1007/bf02542507
|View full text |Cite
|
Sign up to set email alerts
|

Specific limited hydrolysis and phosphorylation of food proteins for improvement of functional and nutritional properties

Abstract: Limited specific hydrolysis of casein by Staphylococcus aureus V8 protease was used to produce 2% and 6.7% hydrolysates (2 and 6.7% of the peptide bonds hydrolyzed), each containing five polypeptides (by gel filtration) ranging in size from -16,000 to -1,000 daltons. The mixtures of polypeptides had substantially increased solubilities at pH 4.0-4.5, near the isoelectric point of casein. In general, the emulsifying activity index was less for the hydrolysates than for casein; the emulsion stability was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…These treatments include heating, pH adjustment, hydrolysis and covalent attachment of other constituents [6]. Many authors [1,4,7,8] have studied the effect of heath treatment under different conditions on different functional properties of soy isolates.…”
Section: Introductionmentioning
confidence: 99%
“…These treatments include heating, pH adjustment, hydrolysis and covalent attachment of other constituents [6]. Many authors [1,4,7,8] have studied the effect of heath treatment under different conditions on different functional properties of soy isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Glu-and Asp specific proteases have been used in peptide mapping studies (Schmidt, 1988). Chobert et al, (1987Chobert et al, ( , 1988) used a Glu-and Asp-specific protease (V8) from Staphylococcus aureus to enhance the solubility and emulsifying properties of casein hydrolysates. Ju et al (1995) found that limited hydrolysis by a Bacillus licheniformis protease (BLP) increased the gel strength of whey protein hydrolysates.…”
Section: Introductionmentioning
confidence: 99%
“…Solubility in water is often enhanced by phosphorylation (Chobert, Sitohy, and Whitaker 1987), but cross-linking reduces it (Matheis et al 1983). Phosphorylation slows down digestibility, but the degree of hydrolysis of phosphorylated casein is almost the same as that of a nonphosphorylated one (Matheis et al 1983).…”
Section: Phosphorylationmentioning
confidence: 97%